Apert syndrome and repercussions in Dental Medicine - Paula, Lígia de (2020)
Apert’s syndrome is a craniosynostosis syndrome caused by mutations in the gene coding for the fibroblast growthfactor receptor 2 (FGFR2), characterized by craniosynostosis, midface hypoplasia and syndactyly of the hands and feet. It has several oral manifestations, such as ogival palate, maxillary transverse and sagittal hypoplasia, dental crowding, eruptive delay and ectopic position of the teeth. The diagnosis of Apert’s syndrome is established in a proband with classic clinical characteristics, and genetic tests can also be performed. Patients with this syndrome often require craniofacial team care and dental, orthodontic and orthognathic surgical management because of their esthetic and functional problems such as Class III malocclusion and midface hypoplasia. The aim of this study is to present a literature review on oral manifestations of Apert’s syndrome and their impact on dental medicine.